HUBUNGAN KADAR TRIASILGLISEROL DARAH DENGAN KADAR HIGH SENSITIVITY C-REACTIVE PROTEIN PADA REMAJA OBES - Melatunan, Melda (e-Biomedik, 2014)
Abstract: Obesity is one of the health problem in the world, also in Indonesia. Obesity is caused by an increased amount of fat that stored in the form triacylglycerol ( TAG ) which is acquired from food. Increase of triacylglycerol level may cause higher risk of cardiovascular disease. High Sensitivity C-Reactive Protein (hs-CRP) is a marker of inflammatory factors that can be used as a marker for cardiovascular disease. This study aimed to determine the correlations between TAG levels on blood and hs-CRP levels on obese adolescents. This study performed by observational analytic study design with the cross-sectional approach. The number of sample in this study were 17 sample who was willing to join. Analysis of bivariate using Spearman nonparametric test. The results showed a significance value ( p ) 0.272 which indicates that the correlation between TAG levels and hs-CRP levels were not significant. Spearman value showed 0.282 that indicates that the direction of a positive correlation with the strength of the correlation is weak. It can be concluded that there is no correlations between TAG levels in blood with hs-CRP levels on obese adolescents. Keyword: Obesity, TAG, hs-CRP, Adolescents Â Â  Abstrak: Obesitas merupakan masalah kesehatan di seluruh dunia, termasuk di Indonesia. Obesitas disebabkan akibat peningkatan jumlah lemak yang disimpan dalam bentuk triasilgliserol (TAG) yang diperoleh dari makanan. Peningkatan triasilgliserol ini akan meningkatkan risiko penyakit kardiovaskuler. High Sensitivity C-Reactive Protein (hs-CRP) merupakan faktor penanda inflamasi yang dapat digunakan sebagai penanda risiko penyakit kardiovaskuler. Penelitian ini bertujuan untuk mengetahui hubungan kadar TAG darah dengan kadar hs-CRP pada remaja obes. Penelitian ini menggunakan desain penelitian analitik observasional dengan pendekatan cross-sectional. Sampel pada penelitian ini berjumlah 17 sampel yang diambil dari seluruh populasi yang bersedia. Analisis bivariat menggunakan uji nonparametrik Spearman. Hasil penelitian didapatkan nilai signifikansi (p) 0,272 yang menunjukkan bahwa korelasi antara kadar TAG dan kadar hs-CRP tidak signifikan. Nilai Spearman sebesar 0,282 menunjukkan bahwa arah korelasi positif dengan kekuatan korelasi yang lemah. Dapat disimpulkan bahwa tidak terdapat hubungan antara kadar TAG darah dengan kadar hs-CRP pada remaja obes. Kata Kunci : Obesitas, TAG, hs-CRP, Remaja